The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/su10082717
|View full text |Cite
|
Sign up to set email alerts
|

Business Ethics as a Sustainability Challenge: Higher Education Implications

Abstract: Recent financial scandals worldwide have intensified concern for business (and especially accounting) ethics. Hence, under an overall economic and social sustainability approach, it is crucial to improve the effectiveness of business ethics and corporate social responsibility (CSR) education, in terms of its impact on business students' awareness of ethical issues. However, stand-alone business ethics/CSR courses are uncommon in Spanish universities. Accordingly, this paper aims at examining the influence of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 68 publications
0
39
0
Order By: Relevance
“…However, existing research has offered mixed findings on this point [14,15,23,26,29]. Simultaneously, little attention has been paid to the contingencies of CSR courses' effectiveness, such as the role of gender [16]. While Ritter showed that females are more positively impacted by business ethics courses [23], it was only true for older (rather than younger) female students [16].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, existing research has offered mixed findings on this point [14,15,23,26,29]. Simultaneously, little attention has been paid to the contingencies of CSR courses' effectiveness, such as the role of gender [16]. While Ritter showed that females are more positively impacted by business ethics courses [23], it was only true for older (rather than younger) female students [16].…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, little attention has been paid to the contingencies of CSR courses' effectiveness, such as the role of gender [16]. While Ritter showed that females are more positively impacted by business ethics courses [23], it was only true for older (rather than younger) female students [16]. To fill this gap, this study explored whether completing a CSR course has a positive impact on undergraduate students' levels of ethical decision-making, and further, whether this impact is stronger for females than for males.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations